Regional differences in the number and type of myenteric neurons of the ileum of rats: a comparison of techniques of the neuronal evidentiation Diferenças regionais no número e tipo de neurônios mientéricos do íleo de ratos: comparação entre técnicas de evidenciação neuronal - Marcílio Hubner Miranda-Neto; Sonia Lucy Molinari; Maria Raquel Marçal Natali; Debora de Melo Gonçalves Sant'Ana (Arquivos de Neuro-Psiquiatria)
We carried out this study with the purpose of analyzing the density of neurons of the myenteric plexus in the mesenteric, intermediate and antimesenteric regions of the ileum of rats. Whole-mounts stained with four different techniques were employed. Through countings under optic microscope in an area of 8.96 mm² we found the following neuronal means with the techniques of Giemsa, NADH-diaphorase histochemistry, NADPH-diaphorase and acetylcholinesterase, respectively: mesenteric region 2144.40±161.05, 1657.80±88.23, 473.80±19.62, 905.25±22.40; intermediate region 1790.60±128.24, 1265.20±141.17, 371.30±27.84, 770.25±33.12; antimesenteric region 1647.0±76.67, 981.80±68.04, 298.50±22.75, 704.50±69.38. We conclude that there is a variation of neuronal density around the intestinal circumference and this fact independs on the technique used to stain the neurons, and that in a single region the neuronal density varies with the technique employed. We also call attention for the identification of the site were countings were carried out, so that the results of research in this area are not compromised. Realizamos este estudo com o objetivo de analisar a densidade de neurônios do plexo mientérico nas regiões mesentérica, intermediária e antimesentérica do íleo de ratos. Empregamos preparados de membrana corados por 4 diferentes técnicas. Através de contagens sob microscópio óptico em uma área de 8,96 mm² encontramos com as técnicas de Giemsa, histoquímica da NADH-diaforase, NADPH-diaforase e acetilcolinesterase, respectivamente as seguintes médias neuronais: região mesentérica 2144,40±161,05, 1657,80±88,23, 473,80±19,62, 905,25±22,40; região intermediaria 1790,60±128,24, 1265,20±141,17, 371,30±27,84, 770,25±33,12; região antimesentérica 1647,0±76,67, 981,80±68,04, 298,50±22,75, 704,50±69,38. Concluimos que há uma variação na densidade neuronal ao redor da circunferência intestinal, e este fato independe da técnica utilizada para marcar os neurônios, e que em uma mesma região, a densidade neuronal varia com a técnica utilizada. Também chamamos a atenção para que seja indicado o local onde as quantificações serão realizadas, para que não haja comprometimento dos resultados em pesquisa nesta área.